Depletion of CD52‐positive cells inhibits the development of central nervous system autoimmune disease, but deletes an immune‐tolerance promoting CD8 T‐cell population. Implications for secondary autoimmunity of alemtuzumab in multiple sclerosis. Issue 4 (3rd January 2017) - von Kutzleben, Stephanie; Pryce, Gareth; Giovannoni, Gavin; Baker, David
Summary: The objective was to determine whether CD52 lymphocyte depletion can act to promote immunological tolerance induction by way of intravenous antigen administration such that it could be used to either improve efficiency of multiple sclerosis (MS) inhibition or inhibit secondary autoimmunities that may occur following alemtuzumab use in MS. Relapsing experimental autoimmune encephalomyelitis was induced in ABH mice and immune cell depletion was therapeutically applied using mouse CD52 or CD4 (in conjunction with CD8 or CD20) depleting monoclonal antibodies. Immunological unresponsiveness was then subsequently induced using intravenous central nervous system antigens and responses were assessed clinically. A dose–response of CD4 monoclonal antibody depletion indicated that the 60–70% functional CD4 T‐cell depletion achieved in perceived failed trials in MS was perhaps too low to even stop disease in animals. However, more marked (~75–90%) physical depletion of CD4 T cells by CD4 and CD52 depleting antibodies inhibited relapsing disease. Surprisingly, in contrast to CD4 depletion, CD52 depletion blocked robust immunological unresponsiveness through a mechanism involving CD8 T cells. Although efficacy was related to the level of CD4 T‐cell depletion, the observations that CD52 depletion of CD19 B cells was less marked in lymphoid organs than in the blood provides a rationale for the rapid B‐cell hyper‐repopulation that occurs following alemtuzumab administration in MS. That B cells repopulate in the relative absence of T‐cell regulatory mechanisms that promote immune tolerance may account for the secondary B‐cell autoimmunities, which occur following alemtuzumab treatment of MS. Abstract : CD52‐depleting monoclonal antibody depletes T and B cells and inhibits the development of relapsing autoimmunity. However, it appears to block the induction of unresponsiveness that can be induced with CD4 T cell depletion and intravenous myelin antigens. This loss of tolerance induction is appears to be mediated by CD8 T cells and may contribute to the secondary B cell autoimmunities caused by alemtuzumab when used in multiple sclerosis.